YOLOv8n–RFID Bottle Sorting with EcoPay for Sustainable Society - Dwi Hastuti Wijaya; Wildan Surya Wijaya; Ahmad Adi Wicaksono; Maharani Wisudawati Swista; Yitno Utomo; Manik Ayu Titisari (Jurnal Teknik Elektro dan Komputer TRIAC, 2026)
The increasing volume of plastic waste requires innovative solutions that integrate technology with sustainable economic incentives. This study presents the development and evaluation of the ECO-PAY system, an automated plastic bottle waste management system that combines YOLOv8n-based object detection with Radio Frequency Identification (RFID) user identification to support circular economy implementation. The system was designed to identify recyclable plastic bottles in real time, authenticate users, and allocate reward points automatically for each valid disposal transaction. Experimental results show that the YOLOv8n model achieved a maximum confidence score of 93.78% with an average detection accuracy of 72.18% in detecting plastic bottles. System performance testing demonstrated stable real-time operation with a frame rate ranging from 6.58 to 14.91 FPS, enabling fast and continuous transactions suitable for public use. In addition, all transaction data, including user identity, object type, and accumulated points, were successfully recorded in a community-based Excel database in a structured and transparent manner. These findings indicate that the ECO-PAY system is technically feasible, reliable, and effective as a smart waste management solution, contributing to sustainable environmental practices and the practical realization of a circular economy model.